FINDING STANDARD DEVIATIONOFA FUZZY NUMBER - Mazarbhuiya, FokrulAlom (International Journal of Research -GRANTHAALAYAH, 2016)
Two probability laws can be root of a possibility law. Considering two probability densities over two disjoint ranges, we can define the fuzzy standard deviation of a fuzzy variable with the help of the standard deviation two random variables in two disjoint spaces.